A mixture theory analysis for reflection phenomenon of homogeneous plane-P1-wave at the boundary of unsaturated porothermoelastic media. Issue 2 (22nd September 2021) - Liu, Hongbo; Dai, Guoliang; Zhou, Fengxi; Cao, Xiaolin
SUMMARY: A mixture theory is employed to analyse the reflection behaviour of a homogeneous plane- P 1 -wave at the boundary of an unsaturated porothermoelastic medium. A non-isothermal dynamic model is employed which takes into account the interaction between the pore fluids and the solid phase of the porous material. In such an unsaturated porothermoelastic cases, the theoretical expressions of the amplitude reflectivity and energy ratio for five kinds of reflected waves generated by the incidence of homogeneous plane- P 1 -wave, that is reflected P 1, P 2, P 3, S and thermal waves, are derived by taking into consideration of the traction-free, water-permeable, air-permeable and adiabatic boundary conditions. The numerical results are obtained and utilized to discuss the relationship between the amplitude reflectivity and energy ratio of each reflected wave and the thermophysical parameters of the unsaturated porothermoelastic media. The results show that the amplitude and energy carried by the incident wave are mainly occupied by reflected P 1 wave and reflected S wave. The amplitude reflectivity and energy ratio of each reflected wave is not just related to the incident angle but also affected by the saturation, thermal expansion coefficient and initial reference temperature. The phase lags of the heat flux and temperature gradient and the thermal conductivity only have a large effect on the amplitude reflectivity and energy ratio of reflected thermal wave.